2012
DOI: 10.1016/j.geomorph.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Records of human occupation from Pleistocene river terrace and aeolian sediments in the Arneiro depression (Lower Tejo River, central eastern Portugal)

Abstract: In the uppermost reach of the Lower Tejo River (eastern central Portugal), where the river crosses two quartzite ridges that separate the Ródão (upstream) and Arneiro (downstream) depressions, Palaeolithic artefacts have been recovered from three lower river terrace levels and a cover unit of aeolian sands. This paper presents data on the discovery of archaeological artefacts from the terrace levels and the aeolian sands that can be linked to Middle and Upper Palaeolithic industries from new field sites at Tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 34 publications
2
37
0
19
Order By: Relevance
“…Correlations by Martins et al (2010b) and Cunha et al (2012), based mainly on geomorphologic criteria and new luminescence dating, indicated that the terrace containing the Lower Palaeolithic industries at Vale do Forno is equivalent to the T4 terrace of the upstream reach III (at Abrantes) and reach I (at R odão) of the Lower Tejo. In these reaches, finite infrared stimulated luminescence (IRSL, from K-feldspar) and optically stimulated luminescence (OSL, from quartz) ages were obtained for the T4, T5 and T6 terrace deposits (Cunha et al, 2008Martins et al, 2010aMartins et al, , 2010b: T4 e ca.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations by Martins et al (2010b) and Cunha et al (2012), based mainly on geomorphologic criteria and new luminescence dating, indicated that the terrace containing the Lower Palaeolithic industries at Vale do Forno is equivalent to the T4 terrace of the upstream reach III (at Abrantes) and reach I (at R odão) of the Lower Tejo. In these reaches, finite infrared stimulated luminescence (IRSL, from K-feldspar) and optically stimulated luminescence (OSL, from quartz) ages were obtained for the T4, T5 and T6 terrace deposits (Cunha et al, 2008Martins et al, 2010aMartins et al, , 2010b: T4 e ca.…”
Section: Previous Studiesmentioning
confidence: 99%
“…This resulted in a significant underestimation for the oldest samples (Cunha et al, 2008;Martins et al, 2009Martins et al, , 2010aMartins et al, , 2010b. Because of this age underestimation issue, Cunha et al (2012) proposed that the T4 aggradation should probably range in age from 340 ka to 160 ka. In the present study, these limitations in luminescence dating are largely overcome by a new protocol that uses the elevated-temperature post-IRIR stimulation (Thomsen et al, 2008;Buylaert et al, 2009) for measuring samples that have the quartz-OSL signal in saturation.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Este hecho también se ha constatado para los valles de los grandes ríos de la fachada atlán-tica del suroeste de Europa (Bridgland et al, 2006) y en concreto para el caso de la Península Ibérica (Santonja & Pérez-González, 1997y 2010Oosterbeek et al, 2010;Cunha et al, 2012). Estos autores indican que las condiciones medioambientales benignas del MIS 11, período cálido interglaciar que comenzó aproximadamente hace 420 ka (Imbrie et al, 1992), favorecieron el incremento de poblaciones con industria achelense en el suroeste de Europa, siendo antes su presencia poco significativa.…”
Section: Interpretaciónunclassified
“…En el curso bajo del río Tajo (Portugal), las dataciones OSL disponibles (Cunha et al, 2008(Cunha et al, , 2012Martins et al, 2009Martins et al, , 2010 indican que las terrazas de c. +30−48 m, con edades de c. 260-340 ka, poseen industrias achelenses (Monte do Famaco), mientras que la terraza inmediatamente inferior (+16−28 m) posee industrias claramente musterienses con fechas comprendidas entre 135 ka (base) y 73 ka (techo), dentro del tránsito Pleistoceno Medio-Superior (MIS 6 -MIS 5). Estas cronologías más recientes son también características de las unidades superiores de las terrazas complejas a +18-20 m en los valles del Jarama y Manzanares (Panera et al, 2011;Pérez-González et al, 2013;Silva et al, 2013).…”
Section: Interpretaciónunclassified